2022
DOI: 10.2147/amep.s377808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical TV Shows on the Surgical Knowledge of Non-Healthcare Students of Lahore, Pakistan

Abstract: Purpose A popular genre of television shows is medical dramas. Although the primary objective of watching these shows is entertainment, acquiring medical knowledge is a passive by-product. Surgical procedures constitute a large part of the storyline of these shows. This could either serve as a source of medical knowledge or provide false information, the effect being especially important in individuals with no prior medical exposure. This study assesses the impact medical TV shows can have on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…These findings could be linked to the themes of the storyline in the drama, such as team medical care. A previous study 20 reported that non-healthcare students who watched medical TV shows with scenes of surgical procedures were more knowledgeable of surgical operations than those who did not, and the increased awareness of the work of hospital pharmacists among high school students and guardians in this study seem to be consistent with this.…”
Section: Discussionsupporting
confidence: 86%
“…These findings could be linked to the themes of the storyline in the drama, such as team medical care. A previous study 20 reported that non-healthcare students who watched medical TV shows with scenes of surgical procedures were more knowledgeable of surgical operations than those who did not, and the increased awareness of the work of hospital pharmacists among high school students and guardians in this study seem to be consistent with this.…”
Section: Discussionsupporting
confidence: 86%